À l’école des palais : les maîtrises de l’écrit parmi les mamelouks des beys de Tunis, des années 1770 aux années 1860 - M’hamed Oualdi (European Journal of Turkish Studies)
In 1840, the governor of Tunis, Ahmed Bey, established a military school within his palace of Bardo allowing some of the servants, the youngest mamlūks, to attend its courses. The Military School combined European military knowledge that was already known to the regular army under mamlūks command, and an Islamic education that had been strengthened within the palace in the 1810s and 1820s. During the first years of the school’s existence, the graduates would not distinguish themselves from the governor’s eldest servants, who benefited from his support and were sometimes autodidacts. Nevertheless, a servant’s rise in rank would usually depend on his individual merits rather than on the academic credentials obtained by his generation. The graduates of Bardo would eventually rise to power, not so much by criticizing the despotic authority, but by transforming the structure of administrative tasks in such a way that the fragmented system of apprenticeship and scribal training was increasingly set aside.